Los sistemas de ecuaciones lineales como instrumento de modelización en la secundaria - Campos Motta, Magaly Ethel (2022)
This report is part of a broader work, whose objective was to build an epistemological reference model for systems of linear equations to fulfill the role of modeling instrument in secondary education and also verify if they satisfy the characteristic features in the sense of Bowl. In this presentation we will focus on showing what it means to adopt algebra as an algebraic modeling tool, through a specific case such as systems of linear equations. This report is part of the Anthropological Theory of Didactics (ADT), of which some theoretical elements are considered, such as algebraic modeling and the features that characterize it. Likewise, we will consider the TAD as a research method. As a result, it was obtained that it is possible to carry out an algebraic modeling through the treatment of systems of linear equations.